Teaching Social and Emotional Learning to Young Learners Through Short Stories: A Conceptual Framework and Practical Guide - Soran Mustafa; Hardi Jasim Hamad (International Journal of Social Sciences & Educational Studies)
This study provides a foundational framework for how Social and Emotional Learning (SEL) can be taught to young learners through short stories. SEL teaches five important skills: self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. This research specifically investigates teaching these skills using the short story “The Little Black Fish”. It aims to evaluate how effectively short stories can develop SEL competencies, thereby enhancing the social and emotional well-being of young learners. The study provides valuable insights into the practical application of SEL competencies in educational settings by providing a framework and a lesson plan sample. Qualitative content analysis was employed, complemented by quantitative analysis to provide a more comprehensive understanding of the samples in the short story. This analysis was based on a template designed around the five competencies developed by the Collaborative for Academic, Social, and Emotional Learning (CASEL). Thirty-one passages from the story were analyzed according to the template. The findings suggest that short stories are an effective tool for promoting SEL skills among young learners. Additionally, the designed template and lesson plan offer a practical guide for teachers teaching SEL through short stories.